Discovery and replication of a peripheral tissue DNA methylation biosignature to augment a suicide prediction model. Issue 1 (December 2016) - Clive, Makena; Boks, Marco; Vinkers, Christiaan; Osborne, Lauren; Payne, Jennifer; Ressler, Kerry; Smith, Alicia; Wilcox, Holly; Kaminsky, Zachary
Abstract Background Suicide is the second leading cause of death among adolescents in the USA, and rates are rising. Methods to identify individuals at risk are essential for implementing prevention strategies, and the development of a biomarker can potentially improve prediction of suicidal behaviors. Prediction of our previously reportedSKA2 biomarker for suicide and PTSD is substantially improved by questionnaires assessing perceived stress or anxiety and is therefore reliant on psychological assessment. However, such stress-related states may also leave a biosignature that could equally improve suicide prediction. In genome-wide DNA methylation data, we observed significant overlap between waking cortisol-associated and suicide-associated DNA methylation in blood and the brain, respectively. Results Using a custom bioinformatic brain to blood discovery algorithm, we derived a DNA methylation biosignature that interacts withSKA2 methylation to improve the prediction of suicidal ideation in our existing suicide prediction model across both blood and saliva data sets. This biosignature was independently validated in the Grady Trauma Project cohort and interacted with HPA axis metrics in the same cohort. The biosignature showed a relationship with immune status by its correlation with myeloid-derived cell proportions in all data sets and with IL-6 measures in a prospective postpartum depression cohort. Three probes showed significant correlations with the biosignature: cg08469255 (DDR1 ), cg22029879 (ARHGEF10 ), and cg24437859 (SHP1 ), of whichSHP1 methylation correlated with immune measures. Conclusions We conclude that this biosignature interacts withSKA2 methylation to improve suicide prediction and may represent a biological state of immune and HPA axis modulation that mediates suicidal behavior.